2021
DOI: 10.1089/fpd.2020.2856
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Whole-Genome Sequencing Infrastructure for Outbreak Detection and Source Tracing of Salmonella enterica Serotype Enteritidis

Abstract: As an important foodborne pathogen, Salmonella enterica serotype Enteritidis is recognized as one of the most common causes of human salmonellosis globally. Outbreak detection for this highly homogenous serotype, however, has remained challenging. Rapid advances in sequencing technologies have presented whole-genome sequencing (WGS) as a significant advancement for source tracing and molecular typing of foodborne pathogens. A retrospective analysis was conducted using Salmonella Enteritidis isolates (n = 65) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Using STs at different MGT levels, 54.8% of the MDR isolates belonged to previously identified MDR-associated MGT STs ( 17 ), with MGT4-ST54, MGT6-ST107, and MGT4-ST354 as the major MDR-associated STs. Interestingly, all these STs belonged to MGT3-ST8, which was one of the dominant types in Asian countries such as China ( 41 , 42 ), South Korea, and Thailand. These findings further confirmed that clade B S. Enteritidis strains isolated in Australia were likely to have originated from other countries, likely from Asia, as part of the global spread of these MDR clones.…”
Section: Discussionmentioning
confidence: 99%
“…Using STs at different MGT levels, 54.8% of the MDR isolates belonged to previously identified MDR-associated MGT STs ( 17 ), with MGT4-ST54, MGT6-ST107, and MGT4-ST354 as the major MDR-associated STs. Interestingly, all these STs belonged to MGT3-ST8, which was one of the dominant types in Asian countries such as China ( 41 , 42 ), South Korea, and Thailand. These findings further confirmed that clade B S. Enteritidis strains isolated in Australia were likely to have originated from other countries, likely from Asia, as part of the global spread of these MDR clones.…”
Section: Discussionmentioning
confidence: 99%
“…Using STs at different MGT levels, 54.8% of the MDR isolates belonged to previously identified MDR associated MGT STs [17], with MGT4-ST54, MGT6-ST107 and MGT4-ST354 as the major MDR associated STs. Interestingly, all these STs belonged to MGT3-ST8, which was one of the dominant types in Asian countries such as China [51, 52], South Korea and Thailand. These findings further confirmed that clade B S .…”
Section: Discussionmentioning
confidence: 99%
“…as the major MDR associated STs. Interestingly, all these STs belonged to MGT3-ST8, which was one of the dominant types in Asian countries such as China [51,52],…”
Section: Amr S Enteritidis In Australiamentioning
confidence: 99%
“…Since 2013, the Chinese Foodborne Disease Surveillance Network has started to adopt the whole-genome sequencing (WGS) approach as the routine toolkit for outbreak investigation and source tracking (Li et al, 2021a). A few Chinese groups used a local integrated WGS infrastructure for foodborne outbreak investigation, including an outbreak caused by Salmonella Enteritidis in this issue (Deng et al, 2021) and by a few other well-recognized pathogens (Chen et al, 2020;Elbediwi et al 2021;Hua et al 2021;Jiang et al, 2020;Wang et al 2021;Wu et al 2021;Xu et al 2020;Yu et al, 2020).…”
Section: Impacts Of Microbial Food Safety In China and Beyondmentioning
confidence: 99%